Implementasi Lean Hospital dalam Menurunkan Waktu Tunggu Obat Pasien Rawat Jalan Instalasi Farmasi RSUD Dr Saiful Anwar (RSSA) Jawa Timur - Widyastuti, Indri; Widya, Reta Anggraeni; Hamidah, Rif'atul; Risnawati, Vina (Pengurus Pusat Ikatan Apoteker Indonesia, 2025)
The minimum service standards (MSS) for drug service- waiting time (26,16%) has not been achieved and the low usage of free delivery services (RAOS SAE) led Pharmacy Department to improve the services with lean hospital management approach. This research aimed to shorten the drug service waiting time at JKN outpatient pharmacy unit with lean hospital management concept. This research was designed with Participation action research (PAR) approach. The data obtained through observations and interviews, analyzed by comparing the waiting time of prescription screening and drug service time with independent t-test comparison. There were 4 wastes resolved out of 8 wastes that successfully identified, They were; flow of personnel and prescriptions which did not match the process (motion and transportation), The time for prescriptions screening (waiting) is too long, and the officer could not do the job effectively because of the slowness of online system. (Non Uti talent). The result of implementation decreased the waiting time of prescription screening from 73 minutes to 61 minutes, and the mean of drug service waiting time decreased from 101 minutes to 63 minutes. Comparing the data before and after lean management application for prescription screening waiting time did not statistically different p>0,05 (p=0,057), this activity increased the usage of RAOS SAE, reducing the number of overtime officer at JKN outpatient pharmacy unit. The implementation of lean hospital management reduced drug service waiting time, even though unachieved the MSS yet. There were external factors that could not be controlled causing insignificant decreases. Several improvements need to be done to achieve the established standards.